Measurement of CSF dynamics with oscillating pressure infusion. (28th December 2012) - Andersson, K.; Manchester, I. R.; Laurell, K.; Cesarini, K. Giuliana; Malm, J.; Eklund, A.
<x xml:space="preserve">Abstract</x> Introduction Infusion tests are used to diagnose and select patients with idiopathic normal pressure hydrocephalus (INPH) for shunt surgery. The test characterizes cerebrospinal fluid dynamics and estimates parameters of the cerebrospinal fluid system, the pressure‐volume index (PVI) and the outflow conductance (Cout). The Oscillating Pressure Infusion (OPI) method was developed to improve the test and reduce the investigation time. The aim of this study was to evaluate the new OPI method by comparing it with an established reference method. Methods Forty‐seven patients (age 71.2 ± 8.9 years) with communicating hydrocephalus underwent a preoperative lumbar infusion investigation with two consecutive infusion protocols, reference (42 min) and new (20 min), that is, 94 infusion tests in total. The OPI method estimated Cout and PVI simultaneously. A real‐time analysis of reliability was applied to investigate the possibility of infusion time reduction. Results The difference in Cout between the methods was 1.2 ± 1.8 μl/s/kPa (ΔRout = −0.8 ± 3.5 mmHg/ml/min), P < 0.05, n = 47. With the reliability analysis, the preset 20 min of active infusion could have been even further reduced for 19 patients to between 10 and 19 min. PVI was estimated to 16.1 ± 6.9 ml, n = 47. Conclusions The novel Oscillating Pressure Infusion method produced real‐time estimates of Cout including estimates of reliability that was in good agreement with the reference method and allows for a reduced and individualized investigation time.